2009
DOI: 10.1037/a0017686
|View full text |Cite
|
Sign up to set email alerts
|

Perception of anticipatory time in temporal discounting.

Abstract: The current article focuses on the role of anticipatory time perception in temporal discounting. We propose a perceived-time-based model and demonstrate that 2 aspects of time perception are relevant to hyperbolic discounting. Specifically, our model states that diminishing sensitivity to longer time horizons (i.e., how long individuals perceive short time horizons to be relative to long time horizons) and the level of time contraction overall (i.e., how long or short individuals perceive time horizons to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 49 publications
10
155
2
Order By: Relevance
“…This perspective is supported by recent neurological research; e.g., [10], [13], [14], [21], [24]. For intertemporal comparison between values of options an element usually taken into account is a certain discounting rate.…”
Section: General Setupmentioning
confidence: 81%
See 4 more Smart Citations
“…This perspective is supported by recent neurological research; e.g., [10], [13], [14], [21], [24]. For intertemporal comparison between values of options an element usually taken into account is a certain discounting rate.…”
Section: General Setupmentioning
confidence: 81%
“…It has been shown that this model is approximated by the wellknown hyperbolic model for shorter time durations or a lower value of the parameter  (for  = 0 by an exact match) and that it is approximated by the exponential model for longer time durations or a higher value of the parameter . Furthermore, it has been explored how this hyperbolic-exponential model relates to an approach assuming a difference between subjective and objective time (following, for example, [14], [20], [23], [25]) and a specific transformation between subjective and objective time, which can be approximated well by a time transformation based on a logarithmic function (e.g., as considered in [23]) or a power function (e.g., as considered in [25]). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations